The Manifestation and Contestation of White Privilege in Multiracial Families: A Disruption - Chandra D. L. Waring (Genealogy, 2025)
“Genealogy is the retrieval of vital and familial data from records of various types, and its ordering into meaningful relationship patterns” (Durie 2017, p [...]